2023
DOI: 10.1007/s00414-023-03060-8
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between decomposition theory and forensic research on postmortem interval

Blake M. Dawson,
Maiken Ueland,
David O. Carter
et al.

Abstract: Knowledge of the decomposition of vertebrate animals has advanced considerably in recent years and revealed complex interactions among biological and environmental factors that affect rates of decay. Yet this complexity remains to be fully incorporated into research or models of the postmortem interval (PMI). We suggest there is both opportunity and a need to use recent advances in decomposition theory to guide forensic research and its applications to understanding the PMI. Here we synthesise knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…A retrospective study found that in 160 studies over the course of 30 years (19 for anthropology, 103 for entomology, and 38 for taphonomy), studies in all three disciplines fell victim to pseudo-replication due to the absence of treatment replication, a problem only rectified by conducting more replication experiments [ 58 ]. To attain sufficient statistical power from studies within the field of taphonomy, researchers need to ensure proper replication of their research [ 59 ]. This involves maintaining spatial independence amongst carcasses, as closely situated carcasses can become interconnected and disperse organisms, potentially leading to the emergence of metacommunities [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study found that in 160 studies over the course of 30 years (19 for anthropology, 103 for entomology, and 38 for taphonomy), studies in all three disciplines fell victim to pseudo-replication due to the absence of treatment replication, a problem only rectified by conducting more replication experiments [ 58 ]. To attain sufficient statistical power from studies within the field of taphonomy, researchers need to ensure proper replication of their research [ 59 ]. This involves maintaining spatial independence amongst carcasses, as closely situated carcasses can become interconnected and disperse organisms, potentially leading to the emergence of metacommunities [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies can moreover implement clothing or alternate locations to respectively investigate forensically relevant scenarios and to help capture the biogeographic variability of Oahu [ 81 , 111 ]. Managing limitations and identifying avenues for further research will be aided by the incorporation of multivariate statistical analysis and emerging theory [ 22 , 81 , [111] , [112] , [113] ]. The current data have great potential for multivariate analyses and these will be prioritized as a more equal distribution of seasons is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The organisms involved in this process range from microbes to insects and vertebrates, forming complex and highly dynamic processes and communities (Benbow et al, 2019). Therefore, estimating the decay rate or the postmortem interval (PMI) remains challenging (Bradford et al, 2014;Brooks, 2016;Dawson et al, 2023;Englmeier et al, 2023;Probst et al, 2020;Woodcock et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of wild boar carcasses has recently been improved with the use of trained dogs and thermal imaging drones (Rietz et al, 2023), but the estimation of the PMI of vertebrate animals is challenging due to the complex dynamics of carrion decomposition. To reduce uncertainty in PMI estimates, as for wild boar carcasses under heterogeneous field conditions, Dawson et al (2023) called for bridging ecological and forensic theory via experiments, modelling and validation. First studies, often with small sample size, revealed a high variation in the decay process but showed clear differences between wild boar and domestic pics (Cho et al, 2021;Probst et al, 2020).…”
Section: Introductionmentioning
confidence: 99%